Simulation of conflict risk for marine traffic within a seaport - Li, Qing (2013)
This research aims to detect and resolve marine traffic conflicts for planning and scheduling of port operators within a busy seaport. A two-stage strategy for conflict resolution is presented. The first stage is the preplanning which will detect and resolve potential conflicts in a deterministic manner using the original schedule of vessel arrivals and departures. The second stage is to take care of the stochastic part due to random fluctuations in real vessel movements. The resolution is to simulate vessel movements and identify applicable corrective measures with multi-link look-ahead conflict prediction. An application of the simulation system is demonstrated using the seaport of Singapore as an example. Simulation results show that traffic conflicts can be effectively resolved with combination of the scheduling method and the simulation-based corrective measures. This research is useful for marine traffic safety management in seaports and also helps enhancing the efficiency of port operations.